FORENSIC ANALYSIS OF COMPLETE HANGING WITH A TYPICAL KNOT POSITION RESULTING IN MECHANICAL ASPHYXIA IN A SUICIDE CASE (CASE REPORT) FORENSIC ANALYSIS OF COMPLETE HANGING - Sihaloho, Kristina; Widyastuti; Peni Kusumasari (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
This case report describes forensic findings in a young male who died due to complete hanging with a typical suspension point. External examination revealed an incomplete, upward-directed ligature mark with a parchment-like appearance, accompanied by facial petechiae. Internal examination demonstrated hemorrhagic infiltration of the neck muscles and visceral petechiae, consistent with mechanical asphyxia. The absence of defensive injuries and supporting situational evidence indicates suicidal hanging. This report highlights the importance of systematic forensic evaluation in distinguishing suicidal hanging from other manners of death. Hanging is the most frequently encountered method of suicide in forensic practice, with the primary mechanism of death being mechanical asphyxia due to compression of the neck structures. This case involves a female victim of complete hanging with a typical suspension point. External examination revealed an incomplete circular pressure abrasion, dark reddish in color, directed upward forming a “V” shape with a parchment-like texture, accompanied by facial petechiae and cyanosis of the lips and fingertips. Internal examination demonstrated hemorrhagic infiltration of the neck skin and muscles, fine froth difficult to break within the airways, and petechial hemorrhages on the heart, lungs, and liver. Based on these findings, the cause of death was determined to be mechanical asphyxia due to hanging. Careful interpretation of such findings is crucial in establishing the cause of death and differentiating suicide from other possible manners of death.